ANALISIS IMPLEMENTASI AKUNTANSI PESANTREN PADA PONDOK PESANTREN NURUH HIDAYAH KEPAHYANG KABUPATEN OGAN KOMERING ILIR - Nurkholis, Kgs. M.; Hendarmin, RM Rum (Jurnal Ecoment Global, 2022)
The purpose of this study was to determine whether the Nurul Hidayah Kepahyang Islamic Boarding School had implemented financial recording and reporting based on the Accounting guidelines of Islamic Boarding Schools. The research method used in this study is a qualitative research method. The data used in this study are primary and secondary data with data collection in the form of observations, interviews and documentation. The data analysis method used is data reduction, data presentation and conclusions from the preparation of financial statements for the last three years. Based on the analysis that has been carried out, the Nurul Hidayah Islamic Boarding School has implemented Islamic Boarding School Accounting Guidelines, although technically it is still assisted by external parties. However, in operational activities up to the process of preparing financial reports, Islamic boarding schools have not used Islamic banks considering that Islamic boarding schools are Islamic-based educational institutions.